Validation of wind resource in 14 locations of Nepal. (April 2018) - Laudari, R.; Sapkota, B.; Banskota, K.
Abstract: In the highly traditional and inefficient energy dependent countries like Nepal effective exploitation of renewable energy need serious attention. In this context, identification of potential locations for wind energy production is the particular interest of Nepal. Wind speed is the most important indicator for assessing the wind energy resource. Wind resource assessment is carried out either by microscale modeling or dedicated masts or by means of both. Measuring wind energy potential by establishing masts demands high cost and longer time period. Hence it is important to validate the available modeled wind speed with the observed data. The modeled wind data produced by High Asia Refined Analysis dataset are validated based on the observed data of 14 locations in this research. Statistical analysis is computed and also wind speed hourly data of all study sites are compared by presenting both sources data graphically. The statistical analysis supports that the two sources of data do not differ significantly and there is moderate correlation between these data sources. The validation result shows that the modeled wind dataset represents moderately the actual wind speed situation of the studied locations. Thus this modeled dataset is useful for preliminary assessment of wind in Nepal. Highlights: Modeled and observed wind speed data have moderate correlation. The two sources of data do not differ significantly. The regression equation does not explain equally in all studied locations. The HAR dataset is useful for wind resource planning in mesoscale in Nepal. Wind resource measurement is useful in only above cut in speed locations.